Estudo cinético da pirólise das macrófitas: Pistia stratiotes e Eichhornia crassipes - Manozzo, Viviane (2016)
The whole world is experiencing an energy crisis, though a lot of potential is wasted because it is necessary to develop technologies for the utilization of biomass as a raw material capable of producing energy. Municipal waste, wood waste, agricultural crop residues, plants and algae, breeding animal waste, food processing and organic waste are considered the main sources of production and biomass and boost research in the energy sector in search responses to the crises faced. The objective of this study was to obtain experimental data of thermal decomposition of biomass Pistia stratiotes and Eichhornia crassipes to determine the kinetic parameters through the pyrolysis process. Thus, laboratory studies were conducted in order to determine the chemical and physical properties: particle size, moisture, volatile matter, ash, cellulose, lignin and superior calorific value (PCS), to obtain the thermal decomposition curve by thermogravimetric analysis for biomasses studied ; and determine the kinetic parameters during pyrolysis of biomass decomposition methods using non-isothermal differential. The thermogravimetric analysis was performed under an inert nitrogen atmosphere at temperatures ranging from 60ºC to 990ºC for four heating rates of 5, 10, 15 and 20 °C / min. Results as 10.83 MJ / kg and 12, 96 MJ / kg were found for PCS of biomasses Pistia stratiotes and Eichhornia crassipes respectively. The determination of the kinetic parameters we used the methods: Flyn Wall Osawa, Kissinger and Friedman. The mass loss of biomass Pistia stratiots presented in the temperature range 244-823 ° C. The Eichhornia crassipes in the range 241-991°C. To Pistia stratiotes the activation energy calculated by the FWO method foinde 178.60 kJ / mol - 332.79 kJ / mol. Kissinger 155.89 kJ / mol. Friedman in the range of 153.75 kJ / mol - 369.09 kJ / mol. For Eichhornia crassipes the activation energy calculated by the method presented FWO in the range of 156.59 kJ / mol - 531 80 kJ / mol. Kissinger 130.46 kJ / mol. Friedman in the range of 156.53 kJ / mol - 349.47 kJ / mol. The results obtained were of the same order of magnitude. The kinetic data confirm that the molecular structures are represented by different mechanisms thermal decomposition reaction rate and the decomposition rate with the temperature in the pyrolysis showing that this technique is a powerful tool for transforming biomass into products which contribute to generation of energy.